Blood flow of bubbles moving in microchannels with bifurcations - Bento, David (2020)
The gas embolism is a well-known phenomenon. Previous studies have been performed to understand the formation, the behavior and the influence of air bubbles in microcirculation. This study aims to investigate the flow of bubbles in a microchannel network with bifurcations. For that purpose, a microchannel network was fabricated by soft lithography. The working fluids used were composed by sheep red blood cells (RBCs) suspended in dextran 40 and two different hematocrits were studied, 5% and 10%. The in vitro blood flow was analyzed for a flow rate of lO ~-tllmin, by using an inverted microscope and a high-speed camera. It was possible to visualize the formation of the bubbles and their behavior along the network. The results show that the passage of air bubbles influences the cells local concentration, since a higher concentration of cells was seen upstream to the bubble and lower concentrations downstream to the bubble.